Pengaruh Perputaran Modal Kerja dan Likuiditas terhadap Profitabilitas Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Hafids Ramadana, Dinda; Siska, Elmira; Indra, Natal (Jurnal Manajemen Riset Inovasi, 2023)
This study aims to analyze the effect of working capital turnover (WCT) and liquidity (CR) on profitability (ROA) in food and beverage companies listed on the Indonesia Stock Exchange in 2019 – 2022. Samples were taken using purposive sampling technique for 31 food and beverage companies. Data is processed using secondary data, then analyzed using descriptive statistics, classical assumption tests and hyphotesis test, The results of the study partially show that working capital turnover (WCT) has a positive but not significant effect on profitability (ROA), while liquidity (CR) has a positive and significant effect on profitability (ROA). Simultaneously, both working capital turnover (WCT) and liquidity (CR) have a significant positive effect on profitability (ROA).